Implementation of Mathematics Learning During the Covid-19 Pandemic Through the G-Suite for Education in Class IX in Odd Semester 2021/2022 Academic Year at Kuaro 1 Public Middle School - Mujahadah, Mujahadah (PT Literasi Nusantara Publisher, 2022)
This study aims to determine the implementation of mathematics learning during the COVID-19 pandemic at SMP Negeri 1 Kuaro. A descriptive qualitative approach is used to analyze the data collected through literature review, observation, and documentation. The object of this research is SMP Negeri 1 Kuaro, namely the process of learning mathematics during the COVID-19 pandemic. The results of this study indicate that learning during the pandemic was carried out well using Google Classroom, Zoom, YouTube, Google form and WhatsApp, during the teacher's Daily Assessment using the google form, and when PTS and PAS were carried out offline. Even though learning is carried out online the teacher continues to carry out lesson plans by making online lesson plans, preparing teaching materials in the form of learning media and preparing teaching materials before the learning process takes place. In carrying out online learning, teachers often use WhatsApp to communicate with students and their parents, besides that WhatsApp is used by teachers to share information related to learning. Meanwhile, in implementing online learning, teachers use Google Classroom, Zoom and YouTube to deliver learning material.